Effects of Nitrogen Fertilization on Soil Nitrogen for Energy Sorghum on Marginal Land in China. (1st March 2017) - Chen, Feng; Ameen, Asif; Tang, Chao‐Chen; Du, Fu; Yang, Xiao‐Lin; Xie, Guang‐Hui
Abstract : Core Ideas: Soil NO3 − –N to a depth of 0 to 90 cm increased significantly as N rate increased. The N rate of 120 kg ha −1 improved dry matter yield with reduced NO3 − –N accumulation. An N surplus seen first at an N rate of 60 kg ha −1 increased as N rate increased. Most inorganic N was required for energy sorghum pre‐anthesis period growth. Nitrogen management is essential for energy crop production maximization on marginal land. This study was conducted to investigate the effects of N fertilizer application rates on temporal–spatial changes in soil inorganic N and N surplus levels on marginal land. Biomass sorghum (variety GN‐11) and sweet sorghum (variety GT‐8) [ Sorghum bicolor (L.) Moench] were planted under five N application rates (0, 60, 120, 180, 240 kg ha −1 ) in Inner Mongolia, China, in 2014 and 2015. With incremental increases in N application rates during each growing season, nitrate nitrogen (NO3 − –N) content in the 0‐ to 90‐cm soil layer for two varieties significantly increased on elongation, anthesis, and harvest dates, while ammonium nitrogen (NH4 + –N) remained stable. The NO3 − –N accumulation in the 0‐ to 90‐cm soil layer at harvest significantly increased from 0 to 240 N kg ha −1 . Larger inorganic N additions were required in the preanthesis period to maximize growth of both varieties compared to the postanthesis period. The apparent N surplus increased as N fertilizer rate increased. The N fertilizer of 120 kg ha −1 improved dry matter yield and relatively reduced NO3 − –N accumulation. Thus, an N rate of 120 N kg ha −1, with an increasing proportion of topdressing N on the elongation date, and a decreasing proportion of basal N on the pre‐seeding date and topdressing N on the anthesis date, could improve biomass yield and reduce N accumulation to achieve more efficient sorghum production on marginal land in Inner Mongolia.